2017
DOI: 10.1128/jb.00665-16
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Damage the Resilience of Fimbriae, Causing Them To Be Stiff and Tangled

Abstract: As adhesion fimbriae are a major virulence factor for many pathogenic Gram-negative bacteria, they are also potential targets for antibodies. Fimbriae are commonly required for initiating the colonization that leads to disease, and their success as adhesion organelles lies in their ability to both initiate and sustain bacterial attachment to epithelial cells. The ability of fimbriae to unwind and rewind their helical filaments presumably reduces their detachment from tissue surfaces with the shear forces that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Antibodies against a fimbrial major structural subunit, unless this major subunit is also the adhesive subunit which is directly involved in bacterial adherence, do not serve as a direct blockage to prevent the recognition between a fimbria and host receptors. A recent study, however, demonstrated that anti-fimbria antibodies, particularly antibodies to ETEC major structural subunits can physically damage fimbria adherence function [23]. Anti-fimbria or anti-major subunit antibodies recognize adjacent major subunits and lock extension and contraction movement of coil-structured fimbriae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against a fimbrial major structural subunit, unless this major subunit is also the adhesive subunit which is directly involved in bacterial adherence, do not serve as a direct blockage to prevent the recognition between a fimbria and host receptors. A recent study, however, demonstrated that anti-fimbria antibodies, particularly antibodies to ETEC major structural subunits can physically damage fimbria adherence function [23]. Anti-fimbria or anti-major subunit antibodies recognize adjacent major subunits and lock extension and contraction movement of coil-structured fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-fimbria or anti-major subunit antibodies recognize adjacent major subunits and lock extension and contraction movement of coil-structured fimbriae. That makes fimbria “stiff and tangled”, resulting in reduction or prevention of ETEC fimbria adherence to host cells [23]. Since the molecular sizes of IgG and more particularly IgA antibodies to CFA major subunits are much larger compared to a typical ETEC tip subunit (15 to 50 kDa), anti-major subunit antibodies recognized the major structural subunits adjacent to the tip subunit can physically prevent a tip from adhering to host receptors (S2 Fig).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalent polyclonal antibodies have also been used to diminish the compliance of CFA/I and coli surface antigen 2 (CS2) pili, which play essential roles in ETEC pathogenesis. These antibodies, which recognize major pilin subunits, decrease pilus resilience during fluid flow by clamping together layers of the helical fiber or two individual pili, thereby increasing their stiffness and entangling them (110,111). The salivary peptide histatin-5 was also found to bind to and stiffen CFA/I pili, inhibiting ETEC colonization in the gastrointestinal tract (112).…”
Section: Other Approachesmentioning
confidence: 99%
“…Bacterial infections are initiated by the attachment of bacteria to their host cells, which is mediated by specialized filamentous structures known as pili (1)(2)(3). As these adhesins are recognized virulence factors, pili have emerged as a target for the development of new vaccines and anti-adhesives (4)(5)(6)(7)(8)(9). In Gram-positive bacteria, pili are assembled as a single polypeptide composed of up to hundreds of pilin protein repeats placed in tandem (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%